2023
DOI: 10.4067/s0718-58392023000200168
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of anthracnose resistant and heat tolerant chili inbreed lines based on morpho-physiological characteristics

Abstract: A better understanding of the various desirable characteristics present in chili (Capsicum annuum L.) genotypes has aided in developing more effective selection methods for crop improvement. Identifying genetically superior parents is critical in selecting the best parents and inbred lines for breeding purposes. This study was conducted over two planting seasons in glasshouse using morpho-physiological parameters to evaluate the heritability variation of selected chili genotypes based on their genetic diversit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
1
0
0
Order By: Relevance
“…[ 2 ]. This study corroborates the findings of [ 32 ], who observed high genetic progress and high heritability in anthracnose-resistant and heat-tolerant chile inbred lines.…”
Section: Resultssupporting
confidence: 92%
“…[ 2 ]. This study corroborates the findings of [ 32 ], who observed high genetic progress and high heritability in anthracnose-resistant and heat-tolerant chile inbred lines.…”
Section: Resultssupporting
confidence: 92%